Raziskovanje vrednostnega sistema interesnih skupin kot izhodišče za usmerjanje urbanizacije podeželja - Golobič, Mojca (Urbani izziv, 2001)
When planning rehabilitation of transitory, rural space, where processes of restructuring agriculture intertwine with urban processes, key definitions concern places where restructuring agriculture and changes in land use are causing degradation and places where further urbanisation or renaturation are the better option. In these definitions it is necessary to follow opinions andgoals of users that are nevertheless difficult to obtain in a mode that canbe directly integrated in standardised rational procedures of physical planning. The presented procedure facilitates the procurement of such knowledge and its transparent integration in local development plans. Thus we can identify interest groups, their viewpoints, and potential conflicts in initial value systems and check their conflicting or harmonising starting points in space.
Keywords: podeželje; razvojna strategija; rural area; sociologija podeželja; urbanizacija; urejanje prostora; vrednote